Children with Special Health Care Needs: A Factual Perspective - Agrawal, Sapna (Journal of Nepalese Association of Pediatric Dentistry, 2020)
Children with special health care needs are present throughout the world, in all nations and all races. As oral health is an integral part of general health, these individuals are at an increased risk of acquiring oral diseases lifelong. Also, oral diseases can have a direct and devastating impact on their quality of life making daily activities more difficult if not treated on time. Managing and treating these differently ables requires increased awareness as well as attention along with specialized training. Establishing an early dental home along with the medical home would help improve their overall quality of life. A planned treatment protocol including proper referral system to the trained professionals would surely help in decreasing the load of oral diseases.